2014
DOI: 10.1155/2014/473919
|View full text |Cite
|
Sign up to set email alerts
|

Extended Surface of Materials as a Result of Chemical Equilibrium

Abstract: A system consisting of at least two components was considered. In this system, nanocrystalline material is formed at high temperature, at which diffusion does not limit the mass transport. The structure results from establishing an equilibrium between surface and volume of the crystallites and their surroundings in isothermal-adiabatic conditions. The surface of each crystallite is covered with another substance. On the basis of the performed energy-balance calculations it was concluded that the reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…nanocrystalline materials whose surface is coated with a twodimensional structure of the adsorbent may be in a state of chemical equilibrium. 44 The results presented in this work show plausible the hypothesis outlined earlier.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…nanocrystalline materials whose surface is coated with a twodimensional structure of the adsorbent may be in a state of chemical equilibrium. 44 The results presented in this work show plausible the hypothesis outlined earlier.…”
Section: Discussionsupporting
confidence: 89%
“…This dependence was used to determine the size distribution of crystallite (GSD) according to the method proposed by Pelka in an article. 44 For this purpose, on the basis of microscopic observations the SEM iron catalyst was assumed to have the size of the nanocrystallites as 10-70 nm and a shape factor S/V as for the sphere. The shares of individual fractions were chosen in such a way that the area under the curve GSD = f (d) was equal to unity for the specified range of diameters of crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the average size of the product nanocrystallites at the beginning of the transformation will be the largest. To sum up, nanocrystallites undergo phase changes in fractions according to their size, and the average size of nanocrystallites of individual phases (substrate/product) after the phase change of individual fractions may change with the progress of the reaction, but the total size distribution (for a sample consisting of 100% of one phase) is practically unchanged (nitriding-reduction reaction cycles: the average size of nanocrystallites is constant) [20,38].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers sought to the lower the internal energy of nanomaterial by decreasing its surface to volume ratio in the sintering processes [16][17][18][19]. However, it has already been shown that nanomaterials can be in the equilibrium state [20], and that industrial catalysts are the best examples of this; the ammonia synthesis iron catalyst maintains its nanocrystalline structure for even more than 15 years despite it working in aggressive atmospheres, under Catalysts 2021, 11, 183 2 of 12 a pressure of 20-30 MPa and a relatively high temperature of 500 • C [21]. In nanocrystalline iron nitriding processes, the minimal nitriding potential is expressed as P 0 = p NH3,pt p 3/2 H2.pt (1) where p NH3,pt is the partial pressure of ammonia, at which phase transformation occurs, and p H2,pt is the partial pressure of hydrogen, at which phase transformation occurs, which is needed to complete transformation of individual nanocrystallites of iron depending on the size of crystallites [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of overheating, the smallest nanocrystallites transform into larger, stable ones, whose active specific surface A is determined by the equilibrium established under given conditions; therefore, the limit values of nanocrystallites with the largest active specific surfaces A max change in the range 0.15–0.10 nm −1 . The size of larger than minimal nanocrystallites remaining in the sample is not the result of the equilibrium state; only the equilibrium between the promoters and the nanocrystallite surface will be established there, but the S/V relationship of the nanocrystallites will not meet the equilibrium conditions [ 53 ]. The largest nanocrystallite in the catalyst does not change as a result of the overheating process, and its active specific surface area A min in each sample is 0.04 nm −1 .…”
Section: Discussionmentioning
confidence: 99%